Between grammar and lexicon - Contini-Morava, Ellen, 1948-; Tobin, Y. (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2000)
This volume has its origins in a theme session entitled: "Lexical and Grammatical Classification: Same or Different?" from the Fifth International Cognitive Linguistics Conference. It includes theme session presentations, additional papers from that conference, and several invited contributions. All the articles explore the relationship between lexical and grammatical categories, both illustrating the close interaction, as well as questioning the strict dichotomy, between them. This volume promotes a holistic view of classification reflecting functional, cognitive, communication, and sign-orie